Investigating the Cytotoxic Effects of Artemisia absinthium Extract on Oral Carcinoma Cell Line - Ioannis Tsamesidis; Aliki Papadimitriou-Tsantarliotou; Athanasios Christodoulou; Dionysia Amanatidou; Chrysostomos Avgeros; Evangelia Stalika; Maria Bousnaki; Georgia Michailidou; Anastasia Beketova; Phaedra Eleftheriou; Dimitrios N. Bikiaris; Ioannis S. Vizirianakis; et al. (Biomedicines)
Background: Artemisia absinthium (A. absinthium), commonly known as absinthe, is a perennial plant with distinctive broad ovate pointed leaves of a silvery-gray color, reaching a height of 1.5 m. The utilization of this herb as a source of natural compounds and as the primary ingredient in the alcoholic beverage absinthe has recently seen a resurgence following a period of prohibition. This study investigates the biological effects of A. absinthium extract on healthy human periodontal ligament stem cells (hPDLSCs) and the human tongue squamous carcinoma cell line (HSC-3). Methods: A. absinthium element characterization was performed using High-Performance Liquid Chromatography (HPLC) and the Folin method. Alizarin assays evaluated the osteogenic capacity of human periodontal ligament cells (hPDLSCs) while CCK-8 and MTT determined the cytotoxicity of the extract against HSC-3 and hPDLSCs. Results: High artemisinin levels were detected, revealing a concentration of 89 μM (25 μg/mL). The total phenolic concentration of the extract was 1.07 mM +/− 0.11. The in vitro cytotoxicity assays revealed the biocompatible profile of the Artemisia extract in hPDLSCs without exhibiting any osteogenic potential. After 24 h of incubation with HSC-3, Artemisia extract (10 µM) decreased cancer cell viability by 99% and artemisinin by 64%, and increased the expression of Caspase 3 and 9 almost six and two times, respectively. Conclusions: In summary, our preliminary findings suggest that A. absinthium extract exhibits a toxic effect against carcinoma cell lines without affecting healthy human periodontal ligament stem cells.